Efektivitas Zoom Cloud Meeting sebagai Media Pembelajaran Bahasa Arab Online di UIN Sunan Ampel Surabaya - Rakhmaddiniah Sulistyawati; Danial Hilmi (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2022)
This study aims to describe the effectiveness of using the Zoom Cloud Meeting application in online lectures for S1 PBA students at UIN Sunan Ampel Surabaya. The research seeks to present data on student recognition regarding their experiences during the distance lecture process by using the Zoom application. There are three main points to be explored, namely familiarity, deliverability and student assessment of the use of zoom as a learning medium. The study used qualitative research methods, where primary data was obtained through online interviews with 30 students. The results of the study concluded that the majority of students felt they were used to using zoom meetings and they could still receive learning well. The majority of students assessed that the main obstacle was the availability of a good network signal. Although there are shortcomings, it can still be concluded that the use of zoom meetings as a learning medium is quite effective, where students can still receive learning well, and learning objectives can be achieved.